Possibilities for improving the cold flow properties of biodiesel fuel by blending with butanol - Makarevičienė, Violeta; Kazancev, Kiril; Kazanceva, Irina (Renewable Energy, 2015)
This report includes an assessment of comparative studies of the cold flow properties of fuel mixtures containing mineral diesel fuel (D), rapeseed oil methyl (RME) or butyl (RBE) esters and butanol (B). The dependence of CP and CFPP on the mixture composition was presented in phase equilibrium diagrams. These experiments established that mixtures in which RME is replaced with RBE have better cold flow properties. Mixtures of any composition meet the requirements for diesel fuel used in the summer period. The concentration of rapeseed oil butyl esters in fuel used in the transitional period may be up to 78%, while for blends containing rapeseed oil methyl esters, the rapeseed oil methyl ester content may only be up to 45%. In the Arctic zone, it is possible to use fuel blends containing up to 10e14% rapeseed methyl esters and up to 18% rapeseed butyl esters.